Soul made flesh : the discovery of the brain - and how it changed the world - Zimmer, Carl, 1966- (Arrow, 2005)
"At the beginning of Europe's turbulent seventeenth century, no one knew how the brain worked. By the century's close, the science of the brain had taken root, unseating centuries-old philosophies of Man and God. Presiding over this evolution was Thomas Willis, a fascinating figure who stands at the centre of an extraordianry group of scientists and philosophers known as the 'Oxford Circle'. Chronicled here in vivid detail are the groundbreaking revelations and experiments that first enshrined the brain as the engine of reason, emotion, and madness - indeed as the very seat of the human soul." - back cover.